Characteristics of Australia's community pharmacies: National Pharmacy Database Project - Berbatis, Constantine; Sunderland, Vivian; Joyce, Andrew; Bulsara, Max; Mills, C. (Pharmaceutical Press, 2007)
Objective: To report the characteristics of community pharmacies in Australia and analyse them for their association with pharmacists' consultation time. Setting: A large representative sample of community pharmacies in Australia in 2002. Method: Questionnaires were mailed by an independent survey group to managers and owners in a national sample of pharmacies stratified into six zones. Questionnaires were returned by 1131 of 1532 pharmacies contacted (73.8%). The data were analysed using the general linear model (GLM) for univariate analysis. Key findings: Male pharmacists comprised 76.3% of pharmacy owners and 39.5% were aged = 51 years. Most pharmacies (81.1%) had one or two pharmacist owners, and 51.3% of pharmacies were members of marketing groups. Medicines accounted for approximately 75% of annual sales and occupied a minority of the average total area of 187.2 m2. Pharmacies opened for an average of 55.5 h per week. Pharmacists spent 18.8% of their time on patient consultation. This was significantly related to pharmacies with forward pharmacy dispensing areas (P < 0.001), which were owner or partner operated (P < 0.002) and had high numbers of customers (P < 0.004). Holding national accreditation status and belonging to a banner group may be additional factors. Conclusions: Ownership of community pharmacies in Australia is dominated by pharmacists in contrast to the minority pharmacist ownership in the USA and England. Owners and managers of pharmacies were mainly male and older than other staff. Pharmacists working in pharmacies with a forward dispensing area, designed to facilitate patient consultation, were significantly more likely to provide increased consultation time for patients. Owner- or partner-operated pharmacies, and pharmacies with high numbers of customers were also significantly associated with patient consultation time. The strength of association between membership of marketing groups and national accreditation with consultation time requires more evidence.